Baicalin alleviates deoxynivalenol-induced intestinal inflammation and oxidative stress damage by inhibiting NF-κB and increasing mTOR signaling pathways in piglets. (June 2020) - Liao, Peng; Li, Yunhu; Li, Meijun; Chen, Xingfa; Yuan, Daixiu; Tang, Min; Xu, Kang
Abstract: This study was conducted to evaluate the intestinal protective effects of baicalin (BAI) in deoxynivalenol (DON)-treated piglets. A total of 320 weaned piglets were randomly allotted to 1 of 4 treatments with 8 replication pens per treatment and 10 piglets per pen. The treatments were basal diet (NC), basal diet + 0.1% baicalin (BAI), basal diet + 4 mg/kg DON (DON), and basal diet + 4 mg/kg DON + 0.1% BAI (DON + BAI). The experiment was conducted for 14 days. BAI supplementation alleviated the impairment of growth performance and the disorder of serum biochemical parameters in DON-challenged piglets. BAI supplementation also alleviated DON-induced negative effects, decreasing protein and gene expression levels of pro-inflammatory cytokines in the serum and intestinal tissue and increasing antioxidant capacity in the serum. BAI increased villus height and villus height/crypt depth but decreased the protein expression levels of nuclear factor kappa B (NF-κB), as determined by immunohistochemical analysis, in the ileum and jejunum. Moreover, we found that BAI inhibited NF-κB and increased mTOR protein and gene expression levels in the serum and intestinal tissues. Collectively, BAI alleviates intestinal inflammatory and oxidative damage by inhibiting NF-κB and increasing mTOR signaling to modulate downstream inflammatory and oxidative responses after DON challenge. Graphical abstract: Image 1 Highlights: Baicalin alleviates deoxynivalenol-induced intestinal inflammation and oxidative stress injury. Baicalin alleviated DON-induced oxidative stress imbalance and inflammatory cytokine disorders. Baicalin alleviated DON-induced damage via inhibited NF- κ B and increased mTOR signaling protein and gene expression.